Improvement in the Analytical Capabilities of LA-ICP-MS for High Spatial Resolution U-Pb Dating of Zircon Using Mixed-Gas Plasma - Liu Shenghua; Wang Xin; Shi Huixia; Zhang Hui; Liu Bingbing (Journal of Analytical Methods in Chemistry)
In this work, a novel method for high spatial resolution U-Pb dating of zircon by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) at 10–16 μm spot diameter has been proposed. This was achieved by introducing 2% (v/v) water-ethanol vapours into ICP in combination with the shielded torch system to increase the sensitivity and suppress the isotopic fractionation effect. Precise and accurate concordant U-Pb ages for Plešovice, GJ-1, and 91500 zircons were obtained using the proposed method, and the results agreed well with the isotope dilution-thermal ionization mass spectrometry (ID-TIMS) and LA-ICP-MS within 2σ, except for the ages obtained using dry plasma at 10 μm spot diameter. Additionally, the effects of plasma condition (dry plasma or 2% (v/v) ethanol plasma) and spot size (10, 16, 24, or 32 μm) on precision (RSD), accuracy (RE), and uncertainty (2σ) of the 206Pb/238U ages have been studied. The results indicated that increasing the spot diameter and introducing 2% (v/v) water-ethanol vapours into ICP significantly improved the precision, accuracy, and uncertainty for small spot diameters (10 and 16 μm), while it exhibited little influence for intermediate spot diameters (24 and 32 μm). Furthermore, the effects of spot size and plasma condition on the precision, accuracy, and uncertainty strongly depended on the sensitivity of analytes.